Makers of the modern theater - Ulanov, Barry (New York : McGraw-Hill, 1961)
- John Gabriel Borkman / Henrik Ibsen ##- To Damascus, Part 1 / August Strindberg ##- Ivanov / Anton Chekhov ##- Hannele / Gerhart Hauptmann ##- Getting married / George Bernard Shaw ##- On Baile's strand purgatory / William Butler Yeats ##- Well of the saints / John Millington Synge ##- Purple dust / Sean O'Casey ##- Hoppla! Such is life! / Ernst Toller ##- Henry IV / Luigi Pirandello ##- Queen and the rebels / Ugo Betti ##- Sodom and Gomorrah ; Song of songs / Jean Giraudoux ##- Antigone / Jean Anouilh ##- Master of Santiago / Henry de Montherlant ##- Ariadne / Gabriel Marcel ##- Bald Soprano / Eugene Ionesco ##- Yerma / Federico García Lorca ##- Long voyage home / Eugene O'Neill ##- Camino Real / Tennessee Williams ##- View from the bridge / Arthur Miller.
boek